Oil rents and non-oil economic growth in CIS oil exporters. The role of financial development - Hasanov, Fakhri J.; Aliyev, Ruslan; Taskin, Dilvin; Suleymanov, Elchin (Elsevier, 2023)
The role of financial development is vital in long-run economic growth. Due to the windfall revenues it might have extra relevance in natural resource-rich developing economies. This study explores whether financial development, measured in the percentage share of the bank loans to the private sector in GDP, can facilitate the impact of oil rents on the development of the non-oil sector in Commonwealth of Independent States oil exporters: Azerbaijan, Kazakhstan, and Russia in the long run. It develops a combined framework where financial development acts as both a threshold variable and an interaction term for the impact of oil rents on non-oil GDP. We find a threshold effect of oil rents for the non-oil sector in Azerbaijan and Kazakhstan. It shows that the same magnitude of oil rents can create more non-oil growth if financial development exceeds 9.6% and 15.5% in Azerbaijan and Kazakhstan, respectively. For Russia, neither threshold nor interaction effects were found – oil rents have a linearly positive impact on non-oil economic development. Moreover, we find that institutional quality fosters non-oil development in Azerbaijan. It also positively affects non-oil development in Kazakhstan and Russia, albeit statistically insignificant. In the design of policies, authorities may wish to implement measures that would lead to the further development of the financial sector and institutional quality to make oil rents more beneficial for the development of the non-oil sector.
Keywords: Financial development -- Economic aspects -- CIS countries.; Economic development -- Effect of oil rents -- CIS countries.; Institutional economics -- CIS countries.; Azerbaijan -- Economic conditions.